2000
DOI: 10.1038/35020115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of cutaneous malignant melanoma by gene expression profiling

Abstract: The most common human cancers are malignant neoplasms of the skin. Incidence of cutaneous melanoma is rising especially steeply, with minimal progress in non-surgical treatment of advanced disease. Despite significant effort to identify independent predictors of melanoma outcome, no accepted histopathological, molecular or immunohistochemical marker defines subsets of this neoplasm. Accordingly, though melanoma is thought to present with different 'taxonomic' forms, these are considered part of a continuous sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
1,187
1
14

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,782 publications
(1,226 citation statements)
references
References 28 publications
24
1,187
1
14
Order By: Relevance
“…Genome-wide analysis of gene expression using microarray technology is proving an important aid in the molecular diagnosis and classification of human malignancies including leukaemias and lymphomas (Golub et al, 1999;Alizadeh et al, 2000), breast cancer (Perou et al, 2000;Sorlie et al, 2001) and melanoma (Bittner et al, 2000). In the current study, we have used a cDNA microarray technique to obtain expression profiles for three diagnostic categories of adult soft tissue sarcomas: synovial sarcomas, leiomyosarcomas and MFHs.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide analysis of gene expression using microarray technology is proving an important aid in the molecular diagnosis and classification of human malignancies including leukaemias and lymphomas (Golub et al, 1999;Alizadeh et al, 2000), breast cancer (Perou et al, 2000;Sorlie et al, 2001) and melanoma (Bittner et al, 2000). In the current study, we have used a cDNA microarray technique to obtain expression profiles for three diagnostic categories of adult soft tissue sarcomas: synovial sarcomas, leiomyosarcomas and MFHs.…”
Section: Discussionmentioning
confidence: 99%
“…powerful tools in this respect, for example, revealing gene sets that allow discrimination of vertical and radial growing CMM and that can be used for class discovery (Bittner et al, 2000;Haqq et al, 2005). Moreover, arrayCGH unraveled genomic aberrations specific for chronic sun-induced melanomas, and indicated that alteration in the CDKN2A and PI3K pathways are independent but complementary events in melanoma pathogenesis (Curtin et al, 2005).…”
Section: G Jönsson Et Almentioning
confidence: 99%
“…Gene expression profiles using cDNA microarrays have been used to derive a useful molecular-based classification for the diagnosis, treatment, and prevention of several cancers (Alizadeh et al, 2000;Bittner et al, 2000). However, biologic systems comprise protein components resulting from transcriptional and post-transcriptional control, post-translational modifications, and protein shifts among different cellular compartments.…”
mentioning
confidence: 99%